ANALISIS PERAN PELAKU USAHA KECIL DAN MENENGAH (UKM) DALAM MENSEJAHTERAKAN MASYARAKAT DI DESA WONOSARI KECAMATAN BENGKALIS - Candra Alfian; Titin Sumarni (Bertuah: Journal of Sharia and Islamic Economics, 2020)
The purpose of this study was to determine whether the role of Small and Medium Enterprises (UKM) is able to prosper the community, the inhibiting factors of Small and Medium Enterprises (UKM) in Wonosari Village, Bengkalis District in developing their business. The research method is descriptive quantitative which aims to systematically and accurately describe the facts of the population. The population in this study amounted to 28 business actors. Data collection techniques using a questionnaire (questionnaire) and documentation. The data analysis technique uses quantitative data analysis techniques using the SPSS application. The results of the study to determine whether the role of Small and Medium Enterprises (UKM) is able to prosper the community, seen from the determination coefficient test of 0.656% = 65.6%. 34.4% (100% -65.6%) influenced by other variables outside this study. The regression coefficient value of the Role of Business Actors is 0.596.This means that the role of business actors is fixed and has an increase, then the Welfare of the Community in Wonosari Village will increase by 0.596. Keywords: Small and Medium Enterprises, UKM.